ПРОСТОРОВЕ ПОШИРЕННЯ ТА УМОВИ ЗАЛЯГАННЯ СЕРЕДНЬОЕОЦЕНОВИХ КОНТИНЕНТАЛЬНИХ ФЛЮВІАЛЬНИХ ВІДКЛАДІВ У МЕЖАХ ІНГУЛЬСЬКОГО МЕГАБЛОКА УКРАЇНСЬКОГО ЩИТА - Kroshko, Yu.V. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2019)
Based on the data of production reports on the geological mapping of individual Sheets of a territory of scale 1: 50,000, a spatial distribution scheme of Middle Eocene continental fluvial deposits has been created. Data on the morphology of the structure of river paleodolines are given. The conditions of occurrence of Middle Eocene continental fluvial deposits in stratified formations within the framework of various sections of paleovalles opening into the Dnieper-Donets depression are studied.